Работы на Правобережном Цимлянском городище в 2003–2006 гг. и процессы его разрушения - Флёров, В.С. (Хазарский альманах, 2020)
The Tsimlyansk fortress on the right-bank of Don is a monument of the Khazar Khaganate in the Lower Don basin, containing ruins of limestone blocks. The fi rst stage of its research took place in 1987, 1988, 1990 at the southern corner of the fortress. Since 2003, the works were transferred to the Eastern wall of the fortress, destroyed by the Tsimlyansk reservoir. From 1952 to 2002, the right Bank of the reservoir collapsed on 140–150 m. 2003–2005 were dedicated exclusively to the determinate the rate of collapse of the shore of the reservoir near the fortress. It is established that the speed is from 10–20 cm to 1.4 m per year. According to forecasts of geomorphologists, for the next 50–75 years the reservoir will completely destroy the settlement. Excavations was concentrated at sector 7, where the preserved section of the Eastern wall of the fortress was found and described.